Zoom Interviews: Benefits and Concessions - John L. Oliffe (SAGE Publishing, 2021)
COVID-19 restrictions have transitioned in-person qualitative research interviews to virtual platforms. The purpose of the current article is to detail some benefits and concessions derived from our experiences of using Zoom to interview men about their intimate partner relationship breakdowns and service providers who work with men to build better relationships. Three benefits; 1) Rich therapeutic value, 2) There’s no place like home, and 3) Reduced costs to extend recruitment reach and inclusivity, highlighted Zoom’s salutary value, the data richness afforded by being interviewed from home, and the potential for cost-effectively progressing qualitative study designs. In particular, reduced labour and travel costs made viable wider reaching participant recruitment and multi-site data collection. The concessions; 1) Being there differently, 2) Choppy purviews and 3) Preparing and pacing, and adjusting to the self-stream revealed the need for interviewers to nimbly adjust to circumstances outside their direct control. Included were inherent challenges for adapting to diverse interviewee locations, technology limits and discordant audio-visual feeds. Amongst these concessions there was resignation that many in-person interview nuances were lost amid the virtual platform demanding unique interviewer skills to compensate some of those changes. Zoom interviews will undoubtedly continue post COVID-19 and attention should be paid to emergent ethical and operational issues.